Minor Millet Phytochemicals and their Pharmacological Potentials - Pujari S, Nivedita; Hoskeri, Joy H (Pharmacognosy Reviews)
Minor millets (MMs) belong to one of the most ancient groups of cereals consumed in different parts of the world. Minor millets are less known grains because of lower cultivation rates and lesser consumption rates. However, MMs area rich source of nutrients, including vitamins, protein, fiber, and starch. GC-MS, LC-MS, and HPLC are commonly used techniques for the phytochemical profiling of MMs. Methanol extracts of MMs have been reported to possess the majority of potential phytochemicals that include flavonoids, terpenoids, sterols, phenols, xanthophylls, xanthinin’s and carotinoids. Some of the most reputed phytochemicals reported include Octadecenoic acid, Stigmasterol, Campesterol, Phthalic acid, Hexadecanoic acid, Ascorbic acid, Luteolin, Tricin. Caffeic acid, r-coumaric acid, xanthophylls, b-cryptoxanthin, Gallic acid, Gentisic acid, Vanillic acid, Kaempferol, Coumaric acid, Sinapic acid, Ferulic acid, Vanillicacid hexoside, p-Hydroxybenzoic acid, Homocitric acid, Caffeic acid, N′, and Apigenin C-dihexoside. These MMs phytochemicals are also reported to exhibit various health benefits, including antioxidant activity, antidiabetic activity, antihyperlipidemic activity etc. Exploring the potential phytochemicals in all known MMs, namely, barnyard millet, kodo millet, foxtail millet, porso millet, and little millet has revealed new insights in understanding these compounds and their potential therapeutic role against disease management.
Keywords: Minormillets; Phytochemicals; Antihyperlipidemia; Antioxidant; Antiproliferative